(untitled) (Global Journal of Human-Social Science, 2021)
This article introduces a new look at hysteria by examining hysterical phenomena from the perspective of Freudian-inspired aesthetics. We will discuss a new femininity brought about by the discovery of hysteria and celebrated by the surrealists as a means of artistic expression, and lastly, we will approach hysteria from the relational standpoint, that is, from the relationships that the hysterical subject establishes with the alterity.